Note—Analyzing Total Factor Productivity with ROI as a Criterion - Miller, David M. (Management Science, 1987)
This research note concerns total factor productivity measurement at the firm level. Specifically the purpose of the note is to describe a means for incorporating return on investment (ROI) as the improvement criterion in profit-linked total factor productivity measurement procedures. The expressions presented here provide a mechanism to explain changes in profits due to productivity performance beyond the level associated with an ROI goal. This is an extension of existing measurement procedures that utilize gross profit margin rather than ROI as the improvement criterion. The formulation presented here is more appropriate than the margin approach when ROI is the primary financial yardstick of the firm. In presenting this formulation, the ROI based expressions for calculating the type of information derived in a profit-linked total factor productivity measurement procedure will first be given. Then the use of these expressions will be illustrated through a case study.